2020
DOI: 10.1038/s41375-020-01065-5
|View full text |Cite
|
Sign up to set email alerts
|

A trispecific killer engager molecule against CLEC12A effectively induces NK-cell mediated killing of AML cells

Abstract: The low five-year survival rate for patients with acute myeloid leukemia (AML), primarily caused due to disease relapse, emphasizes the need for better therapeutic strategies. Disease relapse is facilitated by leukemic stem cells (LSCs) that are resistant to standard chemotherapy and promote tumor growth. To target AML blasts and LSCs using Natural Killer (NK) cells, we have developed a trispecific killer engager (TriKE™) molecule containing a humanized anti-CD16 heavy chain camelid single domain antibody (sdA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 51 publications
0
52
0
Order By: Relevance
“… 13 , 16 , 19 , 20 , 21 Based on these studies, various CLL‐1‐targeted therapies are being developed and tested in clinical trials. 22 , 23 , 24 , 25 , 26 , 27 , 28 In this study, we observed various bimodal expression patterns of CLL‐1 in AML patient samples (Figure 1 A‐C). The bimodal expression can be identified as two distinct (positive vs. negative) populations within the CD34 + AML blasts.…”
Section: Introductionmentioning
confidence: 55%
See 1 more Smart Citation
“… 13 , 16 , 19 , 20 , 21 Based on these studies, various CLL‐1‐targeted therapies are being developed and tested in clinical trials. 22 , 23 , 24 , 25 , 26 , 27 , 28 In this study, we observed various bimodal expression patterns of CLL‐1 in AML patient samples (Figure 1 A‐C). The bimodal expression can be identified as two distinct (positive vs. negative) populations within the CD34 + AML blasts.…”
Section: Introductionmentioning
confidence: 55%
“…Moreover, within the CLL‐1‐positive blasts, only unimodal expression of CLL‐1 was identified 13,16,19‐21 . Based on these studies, various CLL‐1‐targeted therapies are being developed and tested in clinical trials 22‐28 . In this study, we observed various bimodal expression patterns of CLL‐1 in AML patient samples (Figure 1A‐C).…”
Section: Introductionmentioning
confidence: 59%
“…CD16 × NKG2D BiKE displayed increased affinity to CD16 and induced superior leukemia cell killing compared to the engineered NKG2D-Fc fusion protein [186]. Besides, CD16 × CLL-1 × IL-15 TriKE displayed robust NK cell activity against AML in vitro and in vivo [187]. These molecules constitute attractive candidates for personalized immunotherapy for AML based on preclinical findings.…”
Section: Bike and Trikementioning
confidence: 96%
“…The third component is the addition of an IL-15 crosslinker to expand the NK response [ 35 ]. TriKEs with CLEC12A, which is expressed on AML and leukemic stem cells (LSCs), were able to reduce tumor burden in vitro and in mouse models, while successfully sparing HSCs [ 36 ]. In vitro, TriKEs enhanced NK cell cytotoxicity, degranulation, and cytokine release [ 37 ].…”
Section: Mechanism and Structurementioning
confidence: 99%
“…Compared to the CD33 target, the CLEC12A TriKE had fewer off target effects on peripheral blood mononuclear cells (PBMC) with similar efficacy in NK cell activation [ 35 ]. This was further explored in mouse models, demonstrating that the CLEC12A TriKE induced a robust NK cell response, killing AML cells while sparing normal HSCs [ 36 ]. The DART known as CLEC12A-ENG.CD123IL7Ra was synthesized to target CLEC12A with the addition of IL7Ra to the CD123 portion of the DART.…”
Section: Antigen Targetsmentioning
confidence: 99%